The Principles of Tri Hita Karana in Harmonizing Rural Spatial Planning Local Wisdom Based (Study in Bugbug Traditional Village, Karangasem) - Ni Made Jaya Senastri (Jurnal Hukum Prasada, 2023)
In principle, rural spatial planning local wisdom based on a sustainable spatial planning system is an embodiment of immaterial and material harmonization or balance of life between humans and God, between humans and humans and humans and the environment. Local wisdom on spatial planning in rural areas is interpreted as a system of values, culture, politics, law, economics and religiosity which functions to guide patterns of behaviour in understanding space as a place to live. This study aims to examine legal culture as a value system in the formation of the legal system elements and the principle of Tri Hita Karana as a harmonization of spatial planning in Bugbug traditional village. This study used an exploratory method and this type of research is a qualitative descriptive study of law. The results of this study showed that spatial planning of rural areas local wisdom based is very important as a recognition of the rights of rural communities. In fact, spatial planning arrangements for rural areas with local wisdom aim to protect and manage the environment in a sustainable manner for the benefit of every generation and become the basis for planning, utilizing and controlling sustainable spatial planning. The concept of regulating rural spatial planning local wisdom based in managing rural spatial planning local wisdom based through customary village autonomy in the Bugbug Traditional Village is to create spatial planning in favour of village communities through a rural spatial planning model based on traditional villages through implementing the Tri Hita Karana principle in the spiritual environment, social environment, and natural environment.